2017
DOI: 10.1002/jmv.24752
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine response to Hantaan virus infection in patients with hemorrhagic fever with renal syndrome

Abstract: Hantaan virus (HTNV) infection of the human body causes a severe acute infectious disease known as hemorrhagic fever renal syndrome (HFRS). The aim of this study was to correlate patient cytokine profiles to HFRS severity. In this study, we discuss the clinical significance of evaluating HFRS treatment outcomes using cytokine information. The levels of 18 cytokines were quantitatively determined in three groups: 34 HTNV IgM+ cases, 63 HTNV IgM- negative cases, and 78 healthy volunteers. The level of 14 serum c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 30 publications
1
33
0
Order By: Relevance
“…RIG-I, also known as DDX58, was reported to inhibit HTNV replication by facilitating HTNV-induced IFNβ production (Ma et al, 2017). HTNV infection enhanced the production of multiple cytokines, including interleukin (IL) 6 (Jiang et al, 2008;Yu et al, 2014;Guo et al, 2017). Besides, we previously demonstrated that myxovirus resistance 2 (MX2, also known as MXB) served as a potential inhibitor in HTNV infection (Li et al, 2019).…”
Section: Analysis Of Regulatory Network Of De Circrnas Mirnas and Mmentioning
confidence: 99%
“…RIG-I, also known as DDX58, was reported to inhibit HTNV replication by facilitating HTNV-induced IFNβ production (Ma et al, 2017). HTNV infection enhanced the production of multiple cytokines, including interleukin (IL) 6 (Jiang et al, 2008;Yu et al, 2014;Guo et al, 2017). Besides, we previously demonstrated that myxovirus resistance 2 (MX2, also known as MXB) served as a potential inhibitor in HTNV infection (Li et al, 2019).…”
Section: Analysis Of Regulatory Network Of De Circrnas Mirnas and Mmentioning
confidence: 99%
“…Elevated IL‐6 levels in plasma have been associated with more severe HFRS . Elevated levels of IL‐6 and other cytokines such as IL‐8, IL‐10, TNF and IFN‐γ have also been detected in Dobrava virus‐infected and Hantaan virus‐infected HFRS patients and in HPS patients indicating that elevated levels of these cytokines are a general consequence of human hantavirus infection.…”
Section: Inflammatory Responses In Puuv and Other Hantavirus Infectionsmentioning
confidence: 99%
“…Hantaan orthohantavirus (HTNV) is the main causative agent of hemorrhagic fever with renal syndrome (HFRS) in humans, and is the most common etiology of hemorrhagic fevers in Asia. Human HTNV infection has a case-fatality rate as high as 10% [1,2]. HFRS is characterized by elevated levels of proinflammatory cytokines and endothelial cell activation that leads to vascular leakage, thus linking HTNV infection and HFRS with underlying innate immune activation and inflammatory disease.…”
Section: Introductionmentioning
confidence: 99%